(untitled) (CIPEEX, 2025)
The search for an aesthetically harmonious smile is on the rise, and aesthetic restorative treatments can change the shape, color, and texture of teeth, among other things. Direct composite resin restorations have been used conservatively and with excellent results to correct various dental disharmonies, which are the result of patient complaints due to the media bombardment of beauty standards. Objective: To report the clinical case of a patient who presented with lateral incisors with altered shape (conoid), leaving her dissatisfied with her appearance. The indication of composite resin restorations for reanatomization of conoid teeth allows for correction of the shape, restoring the natural appearance of the smile. Case report: Patient MBC, female, attended the UniEVANGÉLICA Dental Clinic complaining of having "thin front teeth that bother me." On intraoral examination, the presence of conoid-shaped upper lateral incisors was noted. Composite resin restorations using the direct technique were proposed to restore the anatomical shape and recover aesthetic harmony. A silicone guide was used, molded in the diagnostic wax-up, thus maintaining the predictability of the previously sculpted tooth anatomy. Conclusions: The shape and size of the lateral incisors were restored with direct composite resin restorations, which provided excellent immediate results and patient satisfaction. The reanatomization procedures were effective in restoring the aesthetics of the teeth with anomalies, providing an aligned smile and improving the patient’s self-image and self-esteem.